A comparative study of labour progress and delivery outcome among spontaneous induced patients - Jayalakshmi, M.; Manisha, G.; Lahari, P.; Hyndavi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Induction of labour is one of the most common procedures during pregnancy. Indications for induction of labour have essentially not changed. The benefit of labour induction must be weighed against the potential maternal or fetal risks associated with the procedure. Objectives were to compare the duration and progress of labour in spontaneous and induced labour, to compare the maternal outcome and fetal outcome, to compare the mode of delivery in spontaneous and induced labour, and to compare the need for oxytocin augmentation. Methods: It was a prospective study conducted in the department of obstetrics and gynaecology, MIMS hospital, Vizianagaram from Jan 2021 to June 2022. Study population consisted of two groups. Results: A total of 300 patients were taken into study. Among them 150 patients were those who went into spontaneous progression and the other 150 included patients who were induced. Women in spontaneous labour had higher chance of full term normal vaginal delivery than women in induced group. Various factors like maternal age, gestational age, parity, were compared between both these groups using a proforma. In our study we found that patient gets into spontaneous labour on an average around 38 weeks. Conclusions: Latent phase and active phase of labour are prolonged in induced patients when compared to that of spontaneous labour. There was an increase in caesarean section rate from 1.3% in induced patients to 23.3% in spontaneous labour patients. Apgar scores of the babies at 5 minutes in the spontaneous group were found to be better than the induced group.